Evaluasi hasil penatalaksanaan penderita obstruksi duodenum kongenital di RSUP Dr Sardjito - ADIPURWADI, Candra ([Yogyakarta] : Universitas Gadjah Mada, 2010)
Background: Congenital obstruction of the duodenum is a common intestinal obstruction was found in neonatal (0-30 days). This form of obstruction is very easy to be established for the diagnosis because the diagnosis is sufficient to make anamnesis, physical examination and plain abdominal image examinations. With more advanced techniques and equipment operation and maintenance support operations led to the reduction in morbidity and mortality of this case. However, death is often associated with other congenital abnormalities that accompany. Method: a retrospective study method was used with data collection between the years 2004 to 2009 with 49 cases in RSUP Dr Sardjito Yogyakarta. Do an evaluation of the differences in the lives of patients being treated on the basis of age coming, weight comes, age pregnancy, surgery, diagnosis of the broadcaster which statistical tests performed by chi square and fisher exact tests. Result: there is another diagnosis affects survival all patients either congenital duodenal obstruction (p: 0010), in patients who performed the operation. There were significant differences about the presence of accompanying diseases in patients who performed the surgery with bowel switching method is different (p = 0020). Conclusion: Life of patients with congenital duodenal obstruction differ significantly based on the presence of other diseases. Shunting action type was not significantly different to the life of the patient.